Transparent nanocellulose metamaterial enables controlled optical diffusion and radiative cooling. Issue 34 (25th June 2020) - Gamage, Sampath; Kang, Evan S. H.; Åkerlind, Christina; Sardar, Samim; Edberg, Jesper; Kariis, Hans; Ederth, Thomas; Berggren, Magnus; Jonsson, Magnus P.
Abstract : We embedded IR-resonant microparticles as visible scatterers and thermal emitters in a transparent nanocellulose composite, to form a metamaterial that provides radiative cooling while simultaneously functioning as an optical diffuser. Abstract : Materials that provide independent control of infrared thermal radiation and haze in the visible could benefit many areas and applications, including clothing, packaging and photovoltaics. Here, we study this possibility for a metamaterial composite paper based on cellulose nanofibrils (CNF) and silicon dioxide (SiO2 ) microparticles with infrared (IR) Fröhlich phonon resonances. This CNF–SiO2 composite shows outstanding transparency in the visible wavelength range, with the option of controlling light diffusion and haze from almost zero to 90% by varying the SiO2 microparticle concentration. We further show that the transparent metamaterial paper could maintain high thermal emissivity in the atmospheric IR window, as attributed to strong IR absorption of both the nanocellulose and the resonant SiO2 microparticles. The high IR emissivity and low visible absorption make the paper suitable for passive radiative cooling and we demonstrate cooling of the paper to around 3 °C below ambient air temperature by exposing it to the sky.